Effects of electromyographic biofeedback interventions for shoulder pain and function: Systematic review and meta-analysis - Kamonseki, Danilo Harudy; Calixtre, Letícia Bojikian [UNESP]; Barreto, Rodrigo Py Gonçalves; Camargo, Paula Rezende (SAGE Publications, 2021)
Objective: To systematically review the effectiveness of electromyographic biofeedback interventions to improve pain and function of patients with shoulder pain. Design: Systematic review of controlled clinical trials. Literature search: Databases (Medline, EMBASE, CINAHL, PEDro, CENTRAL, Web of Science, and SCOPUS) were searched in December 2020. Study selection criteria: Randomized clinical trials that investigated the effects of electromyographic biofeedback for individuals with shoulder pain. Patient-reported pain and functional outcomes were collected and synthesized. Data synthesis: The level of evidence was synthesized using GRADE and Standardized Mean Differences and 95% confidence interval were calculated using a random-effects inverse variance model for meta-analysis. Results: Five studies were included with a total sample of 272 individuals with shoulder pain. Very-low quality of evidence indicated that electromyographic biofeedback was not superior to control for reducing shoulder pain (standardized mean differences = −0.21, 95% confidence interval: −0.67 to 0.24, P = 0.36). Very-low quality of evidence indicated that electromyographic biofeedback interventions were not superior to control for improving shoulder function (standardized mean differences = −0.11, 95% confidence interval: −0.41 to 0.19, P = 0.48). Conclusion: Electromyographic biofeedback may be not effective for improving shoulder pain and function. However, the limited number of included studies and very low quality of evidence does not support a definitive recommendation about the effectiveness of electromyographic biofeedback to treat individuals with shoulder pain.
Keywords: feedback; motor control; Rehabilitation; scapula; subacromial